Life's Simple 7 and the risk of atrial fibrillation: The Multi-Ethnic Study of Atherosclerosis. (August 2018) - Ogunmoroti, Oluseye; Michos, Erin D.; Aronis, Konstantinos N.; Salami, Joseph A.; Blankstein, Ron; Virani, Salim S.; Spatz, Erica S.; Allen, Norrina B.; Rana, Jamal S.; Blumenthal, Roger S.; Veledar, Emir; Szklo, Moyses; et al.
Abstract: Background and aims: We examined the association between the American Heart Association's Life's Simple 7 (LS7) metrics and the risk of atrial fibrillation (AF) in the Multi-Ethnic Study of Atherosclerosis (MESA), a prospective cohort study of adults free of cardiovascular disease (CVD) at baseline. Methods: We analyzed data from 6506 participants. The LS7 metrics (smoking, physical activity, body mass index, diet, blood pressure, total cholesterol and blood glucose) were each categorized into ideal (assigned 2 points), intermediate (1 point) or poor (0 points). Scores were summed for a maximum of 14. A score of 0–8 was considered inadequate; 9-10, average and 11-14, optimal for cardiovascular health. Atrial fibrillation was ascertained using ICD-9 codes from hospital discharge records and Medicare claims data. Cox proportional hazard ratios (HR) and incidence rates of AF per 1000 person-years were calculated. Results: During a median follow-up of 11.2 years (interquartile range: 10.6–11.7 years), 709 (11%) participants were hospitalized with a first AF episode. In the overall cohort, optimal scores at baseline were associated with a 27% lower risk for AF compared with inadequate scores (0.73 [0.59–0.91]). A similar finding was observed when the results were stratified by race/ethnicity (White, Chinese American, African American and Hispanic), though many of the associations were not statistically significant. There was no interaction by race/ethnicity ( p = 0.15). Conclusions: In the overall cohort, optimal LS7 status was associated with a lower risk of AF. These findings suggest that promoting ideal cardiovascular health may reduce the incidence and burden of AF. Highlights: Life's Simple 7 (LS7) are metrics of ideal cardiovascular health (CVH). Higher LS7 scores were associated with a lower atrial fibrillation risk over 11 years. There was no significant interaction by race/ethnicity for these associations. Promoting ideal CVH may reduce the incidence and burden of atrial fibrillation.